Nowe formy turystyki zdrowotnej w podnoszeniu konkurencyjności uzdrowisk - Januszewska, Małgorzata (New forms of health oriented tourism in upgrading spa resorts' competitiveness, 2005)
Health oriented tourism in spa resorts undergoes significant changes. One can observe the emergence of its new forms. Taking advantage of them becomes an important factor in upgrading spa resorts’ competitiveness. The objective of the hereby article is to present a different way of defining forms of health oriented tourism in the world, as well as attempts to specify quality standards for wellness tourism in spa resorts as the basis for upgrading their competitiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 107-117